Application of ergonomic postures during routine dental procedures in a private dental institute - Shravani Deolia; Shivani Dubey; Aditi Chandak; Tanvi Patni; Noopur Padmawar; Sourav Sen (Wolters Kluwer Medknow Publications, 2018)
Introduction: Work-related musculoskeletal disorders are one of the main occupational health hazards affecting dental practitioners. Prolonged sitting and awkward posture can lead to work-related musculoskeletal disorders. This can result in early retirements. Therefore, ergonomic principles should be followed to establish a safe, healthy, and comfortable working environment for dental practitioners, as this also affects the quality of work. Aim: The aim of this study was to evaluate the implementation of ergonomic principles in routine dentistry. Materials and Methods: A single photograph of each practitioner while working on their patient was clicked, and a grid was then developed over these photographs. An assessment form was formulated which was used to evaluate various parameters. The parameters included eye, neck, elbow, upper back, lower back, thigh, and distance of headlight from the oral cavity. Measurements were done manually using ruler and protractor. After assessing all the parameters and determining the values, the evaluation of the results was done using Chi-square test. Results: The photographic analysis was completed by a total of 75 individuals, where 56 (74.6%) were female and 19 (25.3%) of them were male dental practitioners. None of the operators had a correct position of the neck, thus the neck being the most neglected parameter. Only three individuals were observed to follow the correct position of the elbow (P = 0.530). The majority of the individuals failed to position their back (P = 0.098) in the correct manner while performing clinical work. Moreover, it was found that only 15 individuals were following the correct thigh position while operating. Conclusion: Proper implementation of ergonomic principles and maintenance of balanced posture can prevent the occurrence of musculoskeletal disorders and thus increases the work productivity.